Master's Photo Art Project ‘Development of Ukrainian film distribution in Lviv region as a component of film production in Ukraine’ - Oleksandr Bezruchko; Nataliia Kachmar (Вісник Київського національного університету культури і мистецтв. Серія: Аудіовізуальне мистецтво і виробництво, 2022)
The author's idea. The idea of this Master’s Photo Art Project was to draw attention to the development and decay of cinemas in the Lviv region. Cinema, since its inception, has had a great impact on people, his development, formation, more than once has returned the course of history. Cinemas are a place where you can meet its miracle face to face, touch it. However, what is the current state of Ukrainian cinemas? Who still goes there? Can we say, that at the beginning of the internet era, the cinemas are a relic of the past, which now play only a symbolic role? Having watched the cinemas of the Lviv region, communicating with employees and visitors, I tried to answer these questions, first of all for myself. Research on the development of Ukrainian film distribution is very important in modern conditions, as it is an integral component, the basic basis of cinema, which in turn is a priority of public policy in the humanitarian sphere and determined by the Laws of Ukraine ‘On Culture’, ‘On Cinematography’, etc. Successful, profitable film distribution is a financial platform for the development of film production. Therefore, in-depth analysis of ways and directions of film distribution, research of formation conditions and successful realization of its potential, study and coverage of effective principles of film network existence, construction of forecast models of its further functioning are actual and necessary for the social and economic and political development of society.